Pengembangan Mesin 3D Printing Sebagai Alternatif Pembangunan Rumah Yang Lebih Efisien: Pengembangan Mesin 3D Printing Sebagai Alternatif Pembangunan Rumah Yang Lebih Efisien - riyanto adji; Nanang Ali Sutisna; Wan Sen Tjong (Media Teknik Sipil, 2021)
Technological advances will always experience very fast changes, especially in 3D printing technology which is currently acceptable in various industrial worlds, the presence of 3D printing machines really helps humans in visualizing an idea and the results of their thoughts into a very profitable replica. The world of construction has not been fully touched by 3D printing technology, and only a few countries have made it, one of which is the People's Republic of China, which in 2014 succeeded in building a house using a 3D printing machine, with a house size of 40 m2 and 5 floors high. The advantages of building a house with a 3D printing machine include saving labor, saving time in house construction because the construction of a house is determined by the type of concrete and the machine as the main tool, besides that the construction waste generated can be minimized because there is no need to use scaffolding or other tools. the material that is installed is definitely installed neatly because it is arranged in layers. The use of this 3D printing machine will be very useful in Indonesia because it takes into account the high level of population, and the need for housing will be directly proportional to population growth.